2013
DOI: 10.1093/hmg/ddt242
|View full text |Cite
|
Sign up to set email alerts
|

A role of mitochondrial complex II defects in genetic models of Huntington's disease expressing N-terminal fragments of mutant huntingtin

Abstract: Huntington's disease (HD) is a neurodegenerative disorder caused by an abnormal expansion of a CAG repeat encoding a polyglutamine tract in the huntingtin (Htt) protein. The mutation leads to neuronal death through mechanisms which are still unknown. One hypothesis is that mitochondrial defects may play a key role. In support of this, the activity of mitochondrial complex II (C-II) is preferentially reduced in the striatum of HD patients. Here, we studied C-II expression in different genetic models of HD expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 69 publications
(98 reference statements)
2
90
0
1
Order By: Relevance
“…This could represent an age-dependent compensatory mechanism against the well-documented mitochondrial dysfunction in this transgenic mouse model of HD (Damiano et al 2013). However, we could not detect a difference in FL-PGC-1a mRNA expression between 8-week-old wt and tg mice in the cerebellum, which is known to be a relatively resistant region to the degenerative changes in HD (Vonsattel et al 2011).…”
Section: Discussionmentioning
confidence: 88%
“…This could represent an age-dependent compensatory mechanism against the well-documented mitochondrial dysfunction in this transgenic mouse model of HD (Damiano et al 2013). However, we could not detect a difference in FL-PGC-1a mRNA expression between 8-week-old wt and tg mice in the cerebellum, which is known to be a relatively resistant region to the degenerative changes in HD (Vonsattel et al 2011).…”
Section: Discussionmentioning
confidence: 88%
“…It is presently unclear whether defective complex assembly contributes for HD pathology. Indeed, whereas one study reported defective complex II assembly and activity in striatal mitochondria from mice injected with N-terminal mHtt (Damiano et al, 2013), another study reported normal assembly and activity of respiratory complexes in striatal and cortical mitochondria from R6/2 mice (Hering et al, 2015). Nevertheless, other lines of evidence suggest that the direct interaction between mHtt and neuronal mitochondria is a relevant component of HD pathology, contributing to calcium handling defects (Panov et al, 2002), disrupted mitochondrial trafficking (Orr et al, 2008) and excessive mitochondrial fission (Song et al, 2011).…”
Section: Mitochondrial Biogenesismentioning
confidence: 99%
“…Both HD and 3-NP neurotoxicity are characterized by the functional impairment of mitochondrial complex II [1,7]. Disruption of mitochondrial activity is associated with the abnormal production of reactive oxidative species (ROS) like superoxide radical, hydrogen peroxide, hydroxyl radical, peroxyl radical and peroxynitrite, thereby generating oxidative stress [8].…”
Section: Introductionmentioning
confidence: 99%